The Role of Dog Population Management in Rabies Elimination—A Review of Current Approaches and Future Opportunities - Taylor, Louise H.; Wallace, Ryan M.; Balaram, Deepashree; Lindenmayer, Joann M.; Eckery, Douglas C.; Mutonono-Watkiss, Beryl; Parravani, Ellie; Nel, Louis H. (Frontiers in Veterinary Science, 2017)
Free-roaming dogs and rabies transmission are integrally linked across many low income countries, and large unmanaged dog populations can be daunting to rabies control program planners. Dog population management (DPM) is a multifaceted concept which aims to improve the health and well-being of free-roaming dogs, reduce problems they may cause, and may also aim to reduce dog population size. In theory, DPM can facilitate more effective rabies control. Community engagement focussed on promoting responsible dog ownership and better veterinary care could improve the health of individual animals and dog vaccination coverage, thus reducing rabies transmission. Humane DPM tools such as sterilization could theoretically reduce dog population turnover and size, allowing rabies vaccination coverage to be maintained more easily. However, it is important to understand local dog populations and community attitudes towards them in order to determine whether and how DPM might contribute to rabies control, and which DPM tools would be most successful. In practice, there is very limited evidence of DPM tools achieving reductions in the size or turnover of dog populations in canine rabies endemic areas. Different DPM tools are frequently used together and combined with rabies vaccinations, but full impact assessments of DPM programs are not usually available and therefore evaluation of tools is difficult. Surgical sterilization is the most frequently documented tool, and has successfully reduced dog population size and turnover in a few low income settings. However, DPM programs are mostly conducted in urban settings and are usually not government funded, raising concerns about their applicability in rural settings and sustainability over time. Technical demands, costs, and the time necessary to achieve population level impacts are major barriers. Given their potential value, we urgently need more evidence of the effectiveness of DPM tools in the context of canine rabies control. Cheaper, less labor-intensive tools for dog sterilization will be extremely valuable in realizing the potential benefits of reduced population turnover and size. No one DPM tool will fit all situations, but if DPM objectives are achieved dog populations may be stabilized or even reduced, facilitating higher dog vaccination coverages that will benefit rabies elimination efforts.